Miocene Patagonian penguins: craniomandibular morphology and functional mechanics - Haidr, Nadia Soledad; Acosta Hospitaleche, Carolina Ileana Alicia (Alcheringa: An Australasian Journal of Palaeontology)
Fossil penguins (Aves, Spheniscidae) are widely recorded throughout the Southern Hemisphere and are especially well represented from the Eocene to present in Patagonia. There are currently three Miocene specimens that include preservation of part of the skull and mandibles: Paraptenodytes antarcticus, Madrynornis mirandus and MLG 3400 (cf. Spheniscus). Osteological appraisals relative to extant taxa and a morphometric analysis were employed to infer possible dietary preferences. The results suggest that Paraptenodytes antarcticus and cf. Spheniscus were piscivores but used different strategies for prey capture. Madrynornis, on the other hand, might have had a mixed diet comprising both small fish and crustaceans. Fil: Haidr, Nadia Soledad. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina